The Household Integrated Economic Survey of Pakistan 1990-91:Internal and External Consistency (The Pakistan Development Review, 1996)
After the appearance of Morgenstern's The Accuracy of Economic Observations (1950), data quality should be a matter of abiding concern among economists. The present paper highlights the theme by subjecting the Household Integrated Economic Survey (HIES) 1990'91 to a consumer test. From among all remarkable results, a 10 percent "shortfall" of the reported share of workers in agriculture as compared to the Labour Force Survey stands out. Reservations are also made with regard to employment status of workers, income dynamics for employees and self-employed, foreign and domestic reinittances, i(lter-household transfers, improverishment, the marginal propensity to consume, per capita income, and direct tax incidence. If these issues at stake are not inexplicable, at least some elucidation is obviously required. Recommendations for improving HIES data quality emphasise checking on internal and external consistency, and the elucidation of seemingly remarkable results.